Administrasi Pendidikan Islam Bidang Kurikulum MI - Sakban Sakban; Naura Azifa; Nursyafna Nursyafna; Winda Sugiarti; Indah Mutia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study is to analyze school policies in implementing the curriculum in the current era, which uses the Merdeka curriculum and 2013 cirriculum at the ibtidaiyyah madrasah level. The efforts made by this school are to invite teachers to better master learning in the media, and students must certainly also be able to do that. This research method uses qualitative methods, with data collection techniques by observation to schools and interviewing the school or the principal directly also accompanied by documentation. The result of this study is to understand students and the abilities of their students. The implementation of the Merdeka curriculum provides positive hope for the ibtidaiyyah madrasah unit, because it provides flexibility for teachers, so that in carrying out their duties teachers focus on developing the potential of their students. The policy of implementing the Merdeka learning curriculum at the madrasah ibtidaiyyah level is adjusted to the needs of the school and the circumstances of students and the material.